ICT framework for collaborative healthcare services: A case study of Cleft Lip/Palate treatment network in northern Thailand - Noppon Choosri (2018)
© 2016 IEEE. Sophisticated medical treatment often requires multidisciplinary and a number of follow ups. This can limit the opportunity of patient who live in the remoted area to access quality and proper treatment due to the fact that healthcare services in Thailand are relatively centralized by natures. The study proposes the corroborative framework to empower local healthcare cluster to service patient in their area more effectively to minimize patient referral to hub hospital. The study primarily investigates solution for Cleft-Lip/Palate treatment network in Northern Thailand.